PENERAPAN APLIKASI CERDAS PENCEGAHAN STUNTING DI POSYANDU ARUMDALU DESA SANGGRAHAN GROGOL SUKOHARJO - Sari, Devi Pramita; Widodo, Sri; Mustofa, Khoirul; Januar Isnaini, Vina; Muhammad Darmawan, Diki (P3M Universitas Aisyiyah Surakarta, 2025)
Stunting is a condition of failure to achieve normal growth due to poor nutritional status over a long period of time. The purpose of this Community Service Program is to increase the knowledge of stunting cadres through smart applications for stunting prevention. This is the basis for community service with the title